Influência da cobertura de solo sobre a flutuação populacional de Meloidogyne javanica - Soto, Renan Viero Dal (2016)
The Meloidogyne spp. has a vast number of considered species of great agronomical importance. These species provoke high damages in diverse cultures and regions, and are of difficult to keep in control, therefore, majority of the practical ones of handling presents limited efficiency. Ahead of this, the objective of this work is to evaluate the population fluctuation of Meloidogyne javanica during the winter harvest and summer, in seedbeds infested, on different coverings of the ground. The experimental delineation if constituted of blocks to, with four treatments and four repetitions, perhaps being the first treatment alqueive without taken out; the restive of soy; the third o culture of the wheat and the composed room for alqueive with taking out the 20 cm of depth. After the winter handling, established, the culture of the soy. Ground samples had been collected to the 7, 14 and 21 cm and to the 30, 60 and 90 days after the emergency of soy DAE. Each collected sample contained a total of 200cm3/solo. The temperature of the ground was surveyed by sensors connected to a system type to datalogger (Model CR10) in the three depths of collection (7, 14 and 21 cm), during all the period of the experiment. The pluviometric precipitation and the temperature of air had been collected per the climatologic station Agro detect located in Itaara- RS. The variety of soy used in the experiment was to cultivate Nidera 5909. Os parameters taken in the evaluation had been: dry mass and cool aerial part (to the 30, 60 and 90 DAE), stature of plant (to the 30, 60 and 90DAE), number of nematodes for 200 cm³ of ground and 5 grams of root (to the 30, 60 and 90 DAE), and number of galls (to the 30, 60 and 90 DAE). The results had shown that the treatment with alqueive without taking out presented significant effect on the reduction of M. javanica, being clearly that the temperature of the ground and the lack of host had had a direct correlation in the outbreak and infection in the soy root. Already in stubble of the soy, for not presenting peaks of temperatures between the day and the night, and possibly the retention of humidity in the ground, can have contributed for the survival of M. javanica in the ground, therefore, more expressively observed infection accented soon to the 30 DAE in the soy and to the 60 and 90 DAE.